Purity and yield of melanoma exosomes are dependent on isolation method. Issue 1 (1st January 2020) - Shu, Shin La; Yang, Yunchen; Allen, Cheryl L.; Hurley, Edward; Tung, Kaity H.; Minderman, Hans; Wu, Yun; Ernstoff, Marc S.
ABSTRACT: Both exosomes and soluble factors have been implicated in the generation of an immunosuppressive tumour microenvironment. Determining the contribution of each requires stringent control of purity of the isolated analytes. The present study compares several conventional exosome isolation methods for the presence of co-enriched soluble factors while isolating exosomes from human melanoma-derived cell lines. The resultant preparations were analysed by multiplex bead array analysis for cytokine profiles, and by electron microscopy and nanotracking analysis for exosome size distribution and concentration. It is demonstrated that the amount and repertoire of soluble factors in exosome preparations is dependent upon the isolation method used. A combination of ultrafiltration and size exclusion chromatography yielded up to 58-fold more exosomes than ultracentrifugation, up to 836-fold lower concentrations of co-purified soluble factors when adjusted for exosome yield, and a greater than two-fold increase in PD-L1 expressing exosomes. Mechanistically, in context of the immunomodulatory effects of exosomes, the exosome isolation method should be carefully considered in order to limit any effects due instead to co-eluted soluble factors.